2018
DOI: 10.1109/tgrs.2018.2802494
|View full text |Cite
|
Sign up to set email alerts
|

Snow Water Equivalent of Dry Snow Derived From GNSS Carrier Phases

Abstract: Snow water equivalent (SWE) is a key variable for various hydrological applications. It is defined as the depth of water that would result upon complete melting of a mass of snow. However, until now, continuous measurements of the SWE are either scarce, expensive, labor-intense, or lack temporal or spatial resolution especially in mountainous and remote regions. We derive the SWE for dry-snow conditions using carrier phase measurements from the Global Navigation Satellite System (GNSS) receivers. Two static GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…Figure b shows the approximately 5‐m high poles and racks, which were used at the test site Weissfluhjoch and the locations of GPS 1 and GPS 2 . During the snow‐covered season, GPS 2 was covered with snow such that the received GPS signals were influenced by travelling through the snowpack, whereas GPS 1 was permanently above the snow cover since the maximum HS at Weissfluhjoch did not exceed 5 m. This setup is similar to the ones previously described (Henkel et al, ; Koch et al, ). The GPS sensors were installed on 10 October 2015, and the data are still recorded.…”
Section: Study Site and Gps Sensor Setupmentioning
confidence: 77%
See 4 more Smart Citations
“…Figure b shows the approximately 5‐m high poles and racks, which were used at the test site Weissfluhjoch and the locations of GPS 1 and GPS 2 . During the snow‐covered season, GPS 2 was covered with snow such that the received GPS signals were influenced by travelling through the snowpack, whereas GPS 1 was permanently above the snow cover since the maximum HS at Weissfluhjoch did not exceed 5 m. This setup is similar to the ones previously described (Henkel et al, ; Koch et al, ). The GPS sensors were installed on 10 October 2015, and the data are still recorded.…”
Section: Study Site and Gps Sensor Setupmentioning
confidence: 77%
“…This effect is mainly due to signal attenuation in wet snow (Koch et al, ). The values presented in the last column of Table result from an RMSE analysis between DD carrier phase residuals and the fitted arcs as described in Henkel et al (), which are also shown in S1 of the supporting information. Accuracy information on the carrier phase residuals is mainly representative for the SWE calculations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations